Performance of chromium nitride and titanium nitride coatings during plastic injection moulding - Cunha, L. (2002)
Monolithic coatings of chromium nitride, titanium nitride and multilayer titaniumychromium nitride coatings were produced by r.f. and d.c. reactive magnetron sputtering in order to determine their potential to be used as protective coatings for machinery parts of plastic injection moulding or extruding machines. The tribological and mechanical behaviour of these coatings were studied. Monolithic coatings showed lower wear rates, measured by pin-on-disc experiments, when compared with multilayer coatings. The oxidation of the surface was also lower in monolithic coatings. The performance of the coatings during plastic processing was tested in a dye fitted to an injection moulding machine and using glass reinforced thermoplastic. The wear rates of the nitride-based coatings during plastic processing was more than two orders of magnitude better then some traditional methods of protecting the surfaces such as hardening the steel by heat treatment, electrodepositing hard chromium or nitriding the steel surface. The physical vapour deposition coatings also showed higher corrosion protection during plastic processing tests.